Public Sector Budgeting Reforms and Their Impact on Economic Growth: Lessons from Developed and Emerging Economies - Celestin, Mbonigaba; Mishra, Shila (New Perspective: Journal of Business and Economics, 2025)
Public sector budgeting reforms have played a crucial role in shaping economic policies and governance in both developed and emerging economies. This study examines the impact of key budgeting strategies, including performance-based budgeting, zero-based budgeting, digital reforms, participatory budgeting, and gender-sensitive budgeting, on economic growth from 2020 to 2024. Using a comparative analysis and statistical regression models, the study evaluates macroeconomic indicators such as GDP growth rates, fiscal deficits, and budget efficiency indices. The findings indicate a strong positive correlation between budgeting reforms and economic performance, with a correlation coefficient of 0.988 (p = 0.002) in emerging economies and 0.980 (p = 0.003) in developed economies. Regression results confirm that a one-unit increase in budget efficiency leads to a 0.125% GDP growth increase in developed economies (R² = 0.961) and a 0.131% increase in emerging economies (R² = 0.976). Despite significant improvements, emerging economies face challenges related to weak institutional capacity, bureaucratic inefficiencies, and political constraints, necessitating tailored policy interventions. The study recommends adopting digital budgeting tools, enhancing fiscal oversight mechanisms, and integrating participatory budgeting models to improve transparency, efficiency, and long-term economic stability.